Women’s empowerment: examining leadership communication of women entrepreneurs in Indonesia and The USA - Sudarmanti, Rini; Bauwel, Sofie van; Chia Longman (Universiti Kebangsaan Malaysian, 2015)
This article analyses cases of women entrepreneurs’ discourses about their life experiences of empowerment and their leadership communication acts that empower their female subordinates. Compilation of qualitative data fieldwork findings from Bandung, Indonesia were compared with two existing similar studies on women’s entrepreneurship in the US. Despite the cultural and geographic differences of the cases, research findings were generally uniform. Most of the entrepreneurs adopted two primary empowerment approaches related to leadership communications acts: transferring social awareness to encourage self-worth and transferring skills. We generally conclude that women entrepreneurs tend to create open communication, focus on the processes of “listening and persuading,” and show care for others.